2015
DOI: 10.1097/jnr.0000000000000087
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Quality of Life in Adult End-Stage Renal Disease Patients Undergoing Hemodialysis

Abstract: The results of this study indicate that, to improve the QOL in patients with ESRD, comprehensive intervention is necessary to assess and manage depression and fatigue. Social mediation is needed to enhance the QOL of patients with ESRD who lack familial and economic support, those who are single, or those who cannot afford medical expenses either by themselves or with the help of their parents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 14 publications
(22 reference statements)
2
6
0
Order By: Relevance
“…This study found that the factors influencing the QOL of haemodialysis patients were relationship status, employment status, insurance type, and physical and emotional symptoms in Cluster 1, and physical and emotional symptoms in Cluster 2. Tel and Tel () reported that QOL scores were higher in those who were married, those with higher monthly incomes and those whose medical fees were supported by the patients and parents rather than by the government or relatives (Lee, Kim, & Kim, ), while Min et al. () reported that the QOL was better in employed patients.…”
Section: Discussionmentioning
confidence: 99%
“…This study found that the factors influencing the QOL of haemodialysis patients were relationship status, employment status, insurance type, and physical and emotional symptoms in Cluster 1, and physical and emotional symptoms in Cluster 2. Tel and Tel () reported that QOL scores were higher in those who were married, those with higher monthly incomes and those whose medical fees were supported by the patients and parents rather than by the government or relatives (Lee, Kim, & Kim, ), while Min et al. () reported that the QOL was better in employed patients.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, several studies evaluated the QoL in patients on maintenance HD but an integrated assessment of clinical, personological, and adaptation ability parameters has never been approached so far. 21 Moreover, the social context in which the HD patient lives could influence its strategies of adaptation to the chronic illness and dependence on a dialysis machine. 20 …”
Section: Introductionmentioning
confidence: 99%
“…In line with this, a study in Saudi Arabia demonstrated the influence of age on anxiety symptoms among ESRD patients on hemodialysis [15] Moreover, the positive alleviating effect of the higher income on the symptoms of anxiety is very likely given the costs of the ESRD and its management. [16] The present study has also assessed the level of self-esteem among ESRD patients. The results demonstrated that slightly more than onethird of them were having low self-esteem.…”
Section: Discussionmentioning
confidence: 97%